Introduction. (March 2023) - King, Rob
Abstract : This introduction offers an overview of the life and work of Cornell Woolrich, with a particular focus on his place within the crime-fiction mediascape of mid-twentieth-century America. During his lifetime, Woolrich's novels and short stories were adapted at least twenty-one times by Hollywood filmmakers, forty-three times for US television, and seventy-one times for radio. His importance within what Frank Krutnik has called the 'culture of suspense' in 1940s and 1950s America – as well as to the specific formation of film noir – is a given. Yet Woolrich remains an obscure figure in comparison with 'hard-boiled' authors like Dashiell Hammett and Raymond Chandler. This introduction seeks to account for that discrepancy in terms of the different position Woolrich occupied within the era's hierarchies of literary value. It also explores the oft-noted cinematic quality to Woolrich's prose, and the relation of his work to the films of Alfred Hitchcock, whose 1954 Rear Window remains the best-known adaptation of Woolrich's work.